AB0016 Interferon Regulatory Factor 5 (IRF5) Gene Variant Rs2004640 is Associated with Carotid Intimal Medial Thickness in Rheumatoid Arthritis Patients. (10th June 2014) - Vosslamber, S.; Sijl, A.V.; Bos, C.; Voskuyl, A.; Nirmohamed, M.; Verweij, C.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease and is associated with increased cardiovascular (CV) risk. Interferons (IFNs), especially IFNβ, might play a role in atherosclerosis as they are known inhibitors of vascular smooth muscle cell proliferation and intimal hyperplasia. Objectives: We studied whether functional relevant SNPs in the interferon regulatory factor 5 (IRF5) gene are associated with carotic intima media thickness (cIMT), a surrogate maker for CV disease. Methods: In 353 RA patients of the CARRΈ study, IRF5 SNPs rs2004640 and rs4728142 were determined using Taqman Genotyping assay. cIMT was determined in 101 patients by B-mode ultrasonography. Linear regression analyses were used to investigate the association between cIMT and IRF5 genotypes, adjusted for demographic and cardiovascular risk factors. Results: Patients homozygous for rs2004640 G-allele had higher cIMT compared to those homozygote for the T-allele (p=0.019) and a trend towards higher cIMT was observed (p=0.103) for patients homozygous for the rs4728142 G-allele versus patients with the AA-genotype. Age was an effect-modifier for this association. Linear regression analysis in patients older than 60 years showed that the rs2004640 GG-genotype was associated with higher cIMT (regression coefficient 0.107 (C.I. 0.008; 0.205), p=0.035) compared to the TT-genotype. This remained significant after adjustment for traditional risk factors (regression coefficient 0.111 (C.I. 0. 02; 0.202), p=0.020). Conclusions: We demonstrate that IRF5 gene variant rs2004640 is associated with preclinical atherosclerosis in RA patients, independent of traditional cardiovascular risk factors. These results might implicate a role for type I IFN in modulating CV disease features in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4922